Readiness for Change for Teachers in Pandemic Time: Viewed from Leadership and Organizational Culture - Kanya, Nita; Fathoni, Aryo Bima; Wisda, Tri; Nurkholifa, Nahla; Nurjanah, Siti Bunga (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The existence of the COVID-19 pandemic has had a huge impact on human life, one of which is in teaching and learning activities. Both students, teachers, and agencies are required to adapt to the situation and change learning methods to distance learning (online). The purpose of this research is to look for factors that influence teacher readiness for change, especially in terms of leadership and organizational culture. This study uses a quantitative approach to the statistical analysis used in the multiple regression method assisted by the SPSS tool. The measuring instruments used are arranged using a Likert scale based on various theories. From the results obtained, the principal's leadership and organizational culture have a significant influence on teacher readiness for change both partially and simultaneously.